The association between influenza infection and acute myocardial infarction: A comprehensive systematic review and meta-analysis - Xia Zhou; Li Feng (Virus Research)
Influenza infection could be associated with several systemic complications, including acute myocardial infarction (AMI); however, evidence on this association remains inconsistent. This systematic review and meta-analysis examined the influenza-AMI link, temporal AMI risk post-infection, and in-hospital outcomes and mortality in influenza-infected AMI patients. We conducted a systematic search of PubMed, EMBASE, Cochrane Library, Scopus, and Web of Science. Observational studies and self-controlled case series (SCCS) designs, were included. Data were extracted and analyzed using random-effects models to calculate pooled odds ratios (ORs), incidence rate ratios (IRRs), and 95 % confidence intervals (CIs). Subgroup analyses were performed based on exposure definitions (laboratory-confirmed influenza vs. influenza-like illness [ILI]), study design, and temporal patterns of AMI risk. In-hospital outcomes, including mortality, complications, length of stay, and costs, were also evaluated. The meta-analysis included 17 studies. A significant association was found, with a pooled adjusted OR of 2.70 (95 % CI: 1.28–5.72). ILI showed a stronger association with AMI (aOR: 2.04; 95 % CI: 1.33–3.14) compared to laboratory-confirmed influenza. Temporal analyses from SCCS studies revealed a markedly increased risk of AMI within the first week post-infection, peaking in days 1–3 (IRR: 6.83; 95 % CI: 4.66–10.01) and gradually declining thereafter. Influenza-infected AMI patients had significantly worse in-hospital outcomes, including higher mortality (OR: 1.60; 95 % CI: 1.55–1.66), and multiorgan failure (OR: 2.90; 95 % CI: 2.79–3.01). Additionally, these patients experienced longer median hospital stays (8.8 days vs. 5.5 days) and higher hospitalization costs ($20,678 vs. $18,269) compared to non-influenza AMI patients. This study confirms a strong link between influenza and AMI, especially early post-infection. Influenza-infected AMI patients experience worse outcomes, longer hospital stays, and higher costs. These findings highlight the importance of influenza prevention strategies, including vaccination, particularly in high-risk groups, to reduce AMI risk and its cardiovascular burden.